The Unwritten Rules of Phd Research - Petre, Marian; Rugg, Gordon (Berkshire Open University Press, 2004)
"A breath of fresh air - I wish someone had told me this beforehand." PhD student, UK"If you are contemplating a PhD, buy the book and read it straight through to get the larger picture; then re-read each section in greater detail as you tackle each stage of your work.I did the basic research for my PhD in about twelve months, then spent two years writing up the results - and producing possibly too much. It succeeded, but I think I might have made a better job of it if I had read a book like this first. But they didn't exist in those days." MantexThis book looks at things the other books don't tell you about doing a PhD - what it's really like and how to come through it with a happy ending! It covers all the things you wish someone had told you before you started